(untitled) (REMUNOM, 2024)
Experimental classes encourage student learning, observation, investigation of nature and solution of proposed or observed problems. Observation and experimental practice provide, in addition to the understanding of procedures and concepts, the improvement of various cognitive abilities and the understanding of the essence of science. The purpose of the study was to analyze the ripening of fruits without and with plastic and paper packaging, at temperatures of 18 °C and 25 ºC for 16 days, and relate ripening to the production of ethylene gas. The scientific investigation was carried out in two stages, the first stage was carried out addressing the topic hydrocarbons, subtopic alkenes, taught in Organic Chemistry, and the influence of ethylene gas on fruit ripening. In the second stage after the explanation, there was experimentation. Lemons, apples and bananas were used. The fruits at room temperature (control) and at 18 °C were kept at these temperatures for 16 days packed in plastic and paper. After carrying out the experiment, the students filled out a questionnaire about the experiment. Scientific research helps to understand the contents of the Chemistry curriculum and encourages the search for knowledge, awakening interest in the topic, helping to develop new concepts and solutions to problems. Based on the phenomenon and experience, the students were protagonists in the experiment and developed their own conclusions. Scientific research associated common sense and scientific knowledge, producing a scientific explanation and demonstrating the connection between the contents studied in the Chemistry discipline and everyday life.